Implementation and Strengthening of Visible Learning for Elementary School Students’ in Indonesia - Dewantara, Jagat Aditya; Buwono, Sri; Wiyono, Hadi (Jurnal Pendidikan Progresif, 2021)
Implementation and Strengthening of Visible Learning for Elementary School Students in Indonesia. Objectives: The purpose of this study is to describe the strengthening of visible learning in basic education students. Methods: This research uses mixed methods, namely quantitative and qualitative methods. The participants were elementary and junior high school teachers in Sanggau Regency, West Kalimantan Province with a total sample of 50 teachers. Data collection techniques using questionnaires and interviews. Analysis of the data using correlation analysis techniques Moment Product and t-test. Findings: The results of the study found that the implementation of six variables, four variables in the very good category and two in the good category. The relationship between variables between r values of 0.470 to 0.808 shows a strong and positive relationship. Interest analysis shows that the overall value of the variables is very important, and the variables that need strengthening are the variables of students, homes and teaching approaches. Conclusion: The implementation of visible learning factors for elementary education students has been implemented well and very well. Keywords: visible learning, elemenetary school students, mixed method DOI: http://dx.doi.org/10.23960/jpp.v11.i2.202101